2010
DOI: 10.1007/s00422-010-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Relative spike timing in stochastic oscillator networks of the Hermissenda eye

Abstract: The role of relative spike timing on sensory coding and stochastic dynamics of small pulse-coupled oscillator networks is investigated physiologically and mathematically, based on the small biological eye network of the marine invertebrate Hermissenda. Without network interactions, the five inhibitory photoreceptors of the eye network exhibit quasi-regular rhythmic spiking; in contrast, within the active network, they display more irregular spiking but collective network rhythmicity. We investigate the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…The neural correlates of Hermissenda's associative memories formed during lightmovement pairings have been uncovered (Alkon 1980;Crow and Alkon 1980;Britton and Farley 1999;Tamse et al 2003;Cavallo et al 2014). Hermissenda has also been the subject of investigations related to many other aspects of neuroscience, including sensory and motor neuron physiology (Crow and Tian 2004;Nesse and Clark 2010;Jin and Crow 2011;Crow et al 2013) and the evolution of behaviors and neurotransmitter systems Newcomb et al 2012;Lillvis and Katz 2013). A limited number of molecular-level studies have been performed on Hermissenda in these areas (Nelson and Alkon 1988;Crow et al 1997).…”
mentioning
confidence: 99%
“…The neural correlates of Hermissenda's associative memories formed during lightmovement pairings have been uncovered (Alkon 1980;Crow and Alkon 1980;Britton and Farley 1999;Tamse et al 2003;Cavallo et al 2014). Hermissenda has also been the subject of investigations related to many other aspects of neuroscience, including sensory and motor neuron physiology (Crow and Tian 2004;Nesse and Clark 2010;Jin and Crow 2011;Crow et al 2013) and the evolution of behaviors and neurotransmitter systems Newcomb et al 2012;Lillvis and Katz 2013). A limited number of molecular-level studies have been performed on Hermissenda in these areas (Nelson and Alkon 1988;Crow et al 1997).…”
mentioning
confidence: 99%
“…We find that, if the multiplier ν 0 or ν is sufficiently large, only small wave number (long wavelength) solutions are allowed for Z or G. This can be proven for the Euler-Lagrange equations (15), (27), and (32).…”
Section: Dependence Of the Optimal Prcs On The Multipliersmentioning
confidence: 66%
“…5 in Ref. [27]). The authors suggested that the reset effect of such a PRC may be helpful for network information processing.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations